Dynamic Determinants of Korean Productivity Changes: with Emphasis on Trade - Sangho Kim; Hyunjoon Lim (East Asian Economic Review, 2005)
This study investigates the relationship between trade and economic growth in Korea during the period 1980~2003. The empirical results suggest the existence of Granger causality running from imports to total factor productivity (TFP) growth, and the relatively weak causal relationship between exports and TFP. In light of this causal relationship between imports and TFP growth, TFP growth is regressed on various trade variables, along with R&D investments and government size. The results indicate that imports have significant positive effects on TFP but that exports do not. The results also indicate that the salutary impact of imports on TFP growth stems not only from competitive pressure and new knowledge acquired from foreign rivals in the context of increased imports of final goods but also from technological transfers embodied by imports from developed countries. Most of the empirical results still hold when TFP growth is replaced with GDP growth.